Strategy for Sustainable Narrow Rice Field Optimization Through Intercropping of Peanuts Shallots Intercropped with Chili Corn in West Lombok District - Yusuf, M.; Rahayu, Muji; Mulyati, Mulyati (Jurnal Biologi Tropis, 2025)
This aims of study are to: (1) Analyze the impact of the rice-legume-shallot + chili/corn cropping pattern on productivity, farmer income, and sustainability of narrow rice fields in West Lombok Regency; (2) Analyze the optimization of narrow land utilization through a peanut and shallot intercropping system and chili and corn intercropping; and (3) Identify technical and socio-economic constraints in implementing the rice-rice-legume monoculture cropping pattern into a rice-legume-shallot + chili/corn cropping system. The method used in this study is a descriptive method, while data collection was carried out by survey, and analyzed descriptively. The results of the study show that: (1) The rice-legume-shallot + chili/corn cropping pattern in narrow land in West Lombok Regency has a comprehensive positive impact on increasing productivity, cropping index, cost efficiency, and increasing farmer income, as well as supporting land sustainability; (2) Optimizing narrow land through a rotation and intercropping system can increase yields and income sustainably. Integration of crops in one cycle reduces costs, is responsive to climate and markets, and requires technical support, institutions, and access to inputs as prerequisites for the success of a sustainable system; (3) Technical constraints in implementing the rice-legume-shallot + chili/corn cropping system in West Lombok include: agronomic complexity, limited irrigation, pests, technology, and adaptive varieties, as well as socio-economic aspects, including low adoption of innovation, limited capital, high labor, fluctuating prices, minimal market access and institutional support